Allosteric regulation of serine protease HtrA2 through novel non-canonical substrate binding pocket. - Pruthvi Raj Bejugam (Public Library of Science (PLoS), 2013)
HtrA2, a trimeric proapoptotic serine protease is involved in several diseases including cancer and neurodegenerative disorders. Its unique ability to mediate apoptosis via multiple pathways makes it an important therapeutic target. In HtrA2, C-terminal PDZ domain upon substrate binding regulates its functions through coordinated conformational changes the mechanism of which is yet to be elucidated. Although allostery has been found in some of its homologs, it has not been characterized in HtrA2 so far. Here, with an in silico and biochemical approach we have shown that allostery does regulate HtrA2 activity. Our studies identified a novel non-canonical selective binding pocket in HtrA2 which initiates signal propagation to the distal active site through a complex allosteric mechanism. This non-classical binding pocket is unique among HtrA family proteins and thus unfolds a novel mechanism of regulation of HtrA2 activity and hence apoptosis.